Efektivitas Penggunaan Media Video Untuk Pembelajaran Maharah Kalam Di Madrasah Aliyah Nahjatus Sholihin Kelas X - Siti Mahdzuroh (Journal of Innovative and Creativity, 2025)
The purpose of this study was to determine the effectiveness of using video media for learning speaking at Nahjatus Sholihin Islamic Senior High School, tenth grade. This study is a type of quantitative research with an experimental research method, the experimental design used in this study is one group pretest posttest design where researchers test the effectiveness of the video by comparing students' understanding before and after being given treatment. The research sample was taken using a simple random sampling technique, with an error rate of 10% so that a population of 82 could be sampled by 62 students. Based on the results of the output test of normality, it shows that the data is normally distributed, so the researcher conducted data analysis with a paired sample t test which showed that there was a significant difference in learning outcomes between before and after the treatment. The level of effectiveness can be calculated from the N-Gain value. Based on the results of the N-Gain Score test calculation, it shows that video media is less effective on the learning outcomes of speaking.